ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LEVERAGE PADA PERUSAHAAN TAMBANG YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE TAHUN 2009-2012 - Rahmadian Widyarini (Diponegoro Journal of Accounting, 2014)
This research aimed to examine the effect of liquidity, growth opportunities, collateral, dividend payments, profitability, and firm size on leverage which is proxied by Debt to Equity Ratio (DER). DER is a ratio that measures the level of use of corporate debt to total shareholders' equity. While liquidity, growth opportunities, collateral, dividend payments, provitability, and firm size are used as a independent variable.The research uses secondary data which obtained from the Indonesian Capital Market Directory (ICMD) and company annual reports contained in BEI. Determination of the sample using purposive sampling method, which generates 35 mining companies as samples in the period 2009-2012 with a total of 104 observational data. Analyzed data used a multiple linier regression, while hypothesis testing is using F test and t-test.Results showed that during the study period of 2009 to 2012 all variables simultaneously affect the dependent variable. Whereas in partial liquidity, collateral, and profitability have a significant negative effect on leverage. Variable growth opportunities and dividend payments significantly effect with the positive direction on the leverage, while the variable firm size does not have a significant effect on the leverage.